Navigating International Growth : A Comparative Analysis of Equity Entry Modes and Financial Performance in the Auto Sector - Lykhnenko, Oleg (2025)
This thesis examines how external environment factors influence the selection and performance of equity-based entry modes in the global automotive industry. The research focuses on four equity modes - wholly owned subsidiaries, joint ventures, mergers and acquisitions, and strategic alliances - excluding non-equity strategies from the scope. The external analysis part concentrates on the years 2024 and 2025, a period marked by geopolitical tensions, regulatory shifts, economic volatility, and accelerated tech change. A dual qualitative methodology was used, combining external environment analysis through the PESTEL and Porter’s Five Forces models with the evaluation of eight real-world case studies. The findings indicate that external dynamics, such as political risk, regulatory frameworks, market competition, and technological readiness significantly affect both the attractiveness of entry modes and their subsequent success or failure. The thesis is structured into four chapters: the first and second introduce entry mode types and reviews theoretical frameworks; the third presents the methodology and practical analysis; and the fourth outlines the main findings of the thesis. The proposed insights offer valuable guidance for industry leaders and strategic managers seeking to make informed decisions about international expansion under evolving global conditions.